ENGLISH PRONUNCIATION TRAINING - ST. Marhana Rullu; Yusniati N. Sabata; Nurhaida Lakuana (PT. CASA CENDEKIA MEDIA, 2024)
The aim of this activity is to train the English pronunciation of Luwuk Muhammadiyah High School students in Banggai Regency. This activity will be held in November 2022, at Luwuk Muhammadiyah High School, Banggai Regency. The method used in this activity is participatory. Activities are divided into several stages, namely coordination, problem identification, preparation and implementation. The results obtained from this activity were that the implementation of the English Pronunciation Training activity was responded well by the Luwuk Muhammadiyah High School students. This activity increases students' knowledge and skills in supporting learning activities in English subjects.